2020
DOI: 10.1111/rda.13634
|View full text |Cite
|
Sign up to set email alerts
|

Association of SNPs in GnRH gene with sperm quality traits of Chinese water buffalo

Abstract: Hypothalamic gonadotropin‐releasing hormone (GnRH) controls the activity of hypothalamic–pituitary–gonadal axis and plays a key role in the reproductive performance of animals. In this study, five single nucleotide polymorphisms (SNPs), namely g.991T > C, g.1041T > C g.3424T > C, g.3462C > A and g.3463Inde A, were detected in the GnRH gene of 162 water buffaloes by Sanger sequencing. Each SNP was associated with more than two sperm quality traits of ejaculate volume, sperm concentration, post‐thaw sperm motili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Du QZ (2011) demonstrated that for A883G of GnRH gene, the original sperm activity of individuals with AB genotype was far higher than that with BB genotype in Holstein cattle, based on which, he deduced that A allele might be positively related with characteristics of original sperms. Wang et al (2020) found a remarkable association between the SNPs of GnRH and sperm quality traits of Chinese water buffalo. found a highly significant association between G840327C of the GnRH-I gene and age at first egg (AFE) (p<0.01) in a Chinese chicken population.…”
Section: Association Analysis Between Gnrh Gene and Growth Traitsmentioning
confidence: 96%
See 1 more Smart Citation
“…Du QZ (2011) demonstrated that for A883G of GnRH gene, the original sperm activity of individuals with AB genotype was far higher than that with BB genotype in Holstein cattle, based on which, he deduced that A allele might be positively related with characteristics of original sperms. Wang et al (2020) found a remarkable association between the SNPs of GnRH and sperm quality traits of Chinese water buffalo. found a highly significant association between G840327C of the GnRH-I gene and age at first egg (AFE) (p<0.01) in a Chinese chicken population.…”
Section: Association Analysis Between Gnrh Gene and Growth Traitsmentioning
confidence: 96%
“…Hameed et al (2020) discussed influences of GnRH gene and short-term progesterone combined with electrocardiogram (ECG) on reproduction parameters of anestrous Beetal goat during the nonbreeding stage. Wang et al (2020) found a remarkable association between the SNPs of GnRH and sperm quality traits of Chinese water buffalo. found a highly significant association between G840327C of the GnRH-I gene and age at first egg (AFE) (p<0.01) , but no significant association was detected between G840327C and egg number at 300 days of age (p>0.05) in a Chinese chicken population.…”
Section: Introductionmentioning
confidence: 96%
“…Five SNP markers have been identified and are closely correlated with sperm freeze-thawed consistency and possible GnRH gene polymorphism in Chinese water buffalo. An association study found that g.3424T > C and g.3462C > A were used as high ejaculate volume markers, while g.991T > C, g.1041T > C, g.3424T > C, and g.3462C > A were used for decreasing sperm abnormality markers (115). Although evidence is present among the 3-UTR variants of the targeted mRNA, an association with semen quality has been shown (116).…”
Section: Single Nucleotide Polymorphisms Markers Can Be Used For the mentioning
confidence: 99%
“…It was a study in Chinese water buffalo recorded a significant correlation between ejaculate volume of the sperm and single nucleotide polymorphisms (SNPs) in the GnRHR gene (12). Recently, another study in Chinese water buffalo by Wang et al (13) showed a significant association between the SNPs of GnRH and sperm quality. Therefore, the authors recommended the working on additional animal breeds to confirm whether the GnRH gene is the major gene that can influence semen qualities.…”
Section: Introductionmentioning
confidence: 99%